Inferring tumor age from multiple neutral evolutionary process (2019)
Background: All cancer arise as a result of a somatic mutation, several models have been developed to understand cancer, it has been seen as an evolutionary process in which somatic mutations are the pieces of the puzzle. Somatic mutation catalogue of the cancer genome has been used to reconstruct cancer phylogeny, in this case somatic mutations without selective pressure will help determine the age of a tumor. Results: Any type of mutation can have an impact on the cell, the majority of them are neutral, mutations that have less functional impact, that means less selective pressure on the tumor evolution are the ones used as temporal measurement of the tumors. A positive correlation was found between two types of measurements, which shows that an appropriate age can be extracted using both of them. Conclusion: The use of this method can be coupled with other cancer analysis, for example, along with co-occurrence and mutual exclusivity analysis could bring a better understanding of the tumor, an appropriate tumor classification and with this a more accurate clinical decision, which leads to an efective treatment.